Septic arthritis with concomitant gouty arthritis - Govind S Shiddapur; Madhulika Mahashabde; Kavyachand Yalamudi; Swaraj F Shelke (Wolters Kluwer Medknow Publications, 2015)
Gouty arthritis is a rare but serious complication of Septic arthritis and presents a diagnostic difficulty. We report a rare case with co-existence of Acute Inflammatory Gouty Arthritis with septic arthritis clinically. A 40 year old male patient with complaints of fever with chills since one month and multiple joint pains. On examination of joints, swelling and redness of the large joints of both lower limbs was present, more in knee joints involving right knee predominantly than left knee and tenderness was present on palpation of both knee joints. Synovial fluid was diagnostic of septic arthritis. Thus our patient was diagnosed to have Septic Arthritis with concomitant Acute Gouty Arthritis and treated accordingly.